2004
DOI: 10.1051/0004-6361:20034303
|View full text |Cite
|
Sign up to set email alerts
|

XMM–Newtonobservations of the ultraluminous nuclear X-ray source in M 33

Abstract: Abstract. We present observations with XMM-Newton of M 33 X-8, the ultraluminous X-ray source (L 0.5−10 keV ≈ 2×10 39 erg/s) closest to the centre of the galaxy. The best-fit model is similar to the typical model of Galactic black holes in very high state. Comparison with previous observations indicates that the source is still in a very high state after about 20 years of observations. No state transition has been observed even during the present set of XMM-Newton observations. We estimate the lower limit of t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
49
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 56 publications
8
49
0
Order By: Relevance
“…McClintock & Remillard Furthermore, the IMBH model is not the only model that fits ULX spectra. Several sources have been identified in which a variant of this model, where the disc component fits to the hard end of the spectrum, provides a far superior fit (Stobbart, Roberts & Warwick 2004;Foschini et al 2004;Feng & Kaaret 2005). As discussed by Roberts et al (2005) this variant of the empirical black hole spectrum model does not provide a physical model for the X-ray emission -for example there cannot be sufficient photons present in the vicinity of the black hole to produce the dominant soft power-law through Compton up-scattering.…”
Section: The Imbh Model and Other Solutionsmentioning
confidence: 99%
“…McClintock & Remillard Furthermore, the IMBH model is not the only model that fits ULX spectra. Several sources have been identified in which a variant of this model, where the disc component fits to the hard end of the spectrum, provides a far superior fit (Stobbart, Roberts & Warwick 2004;Foschini et al 2004;Feng & Kaaret 2005). As discussed by Roberts et al (2005) this variant of the empirical black hole spectrum model does not provide a physical model for the X-ray emission -for example there cannot be sufficient photons present in the vicinity of the black hole to produce the dominant soft power-law through Compton up-scattering.…”
Section: The Imbh Model and Other Solutionsmentioning
confidence: 99%
“…The brightest source (X-8 in the nomenclature of Long et al 1981, luminosity of 10 39−40 erg s −1 ) is the most luminous X-ray source in the Local Group of galaxies and coincides with the optical center of M 33. Its time variability (Dubus et al 1997), its point-like nature seen by ROSAT HRI (Pietsch & Haberl 2000) and Chandra (Dubus & Rutledge 2002) and its X-ray spectrum best described by an absorbed power law plus disk blackbody model (e.g., Ehle et al 2001;La Parola et al 2003;Foschini et al 2004), point towards a black hole XRB. A possible periodicity of 106 days was not confirmed in later observations (see Parmar et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…(a) Spectral properties -As far as the spectral properties are concerned, Foschini et al (2002a) give ULX photon indices from 1.1 to about 2.3, with an average of about 1.9. This close to the canonical value for broad line, unabsorbed AGN according to Piconcelli et al (2002).…”
Section: Observational Evidence Bearing On This Hypothesismentioning
confidence: 99%
“…(f) The source in NGC 4698 - Foschini et al (2002b) have reported that they have found what they call a background BL Lac object with z = 0.43 in NGC 4698 (z = 0.0033). This clearly can be interpreted as evidence for a local QSO with an intrinsic redshift of 0.43 being ejected from NGC 4698.…”
Section: Letter To the Editormentioning
confidence: 99%
See 1 more Smart Citation